Factors Influencing the Incidence of Stunting: A case-control study at Balikpapan Primary Healthcare - Marini, Rina; Wisnuwardani, Ratih Wirapuspita; Rohmah, Nur (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a serious health issue in Indonesia, with long-term impacts on children's development. SSGI 2022 data shows a national prevalence of 21.6%, down from the previous year but still above the WHO standard and the 2024 target. In East Kalimantan, the prevalence of stunting reached 23.9% in 2022, up from the previous year and a concern as the province will become the new capital city. Stunting impacts brain development and the risk of long-term chronic diseases, influenced by maternal education and employment, as well as limited nutritional knowledge and parenting time. This analytical observational study with a case-control design was conducted in December 2023 at Gunung Sari Ulu Primary Healthcare working area with 30 respondents (15 cases, 15 controls) selected by purposive sampling. Data were collected through questionnaires and assessment of children's nutritional status measurements using a microtoise and infantometer . Stunting is defined as a height or length below -2 SD (WHO). Data analysis was performed using chi-square tests to assess the relationship between variables. No association was found between child gender and stunting (P-value = 1). Mothers with low education levels had a 1.313 times higher risk of having stunted children (P-value = 0.713). Although not statistically significant, non-working mothers had a 2.364 times higher risk of having stunted children compared to working mothers (P-value = 0.651). No significant relationship was found between child gender and stunting incidence. Maternal education and employment status are identified as risk factors for stunting, although not statistically significant.